EVALUATION OF THE EFFECTS OF VARIOUS FACTORS ON ABOVEGROUND AND BELOWGROUND BIOMASS STORAGE CAPACITY OF EASTERN MEDITERRANEAN MAQUIS VEGETATION - Durkaya, Ali; Durkaya, Birsen; Sabanci, Ali; Kaptan, Sinan; Kaptan, Sinan; Durkaya, Birsen; Durkaya, Ali (Croatian Forestry Soc, 2017)
This study was carried out on the data obtained from 35 plot areas selected among the vertical distribution regions of maquis in study area located in Eastern Mediterranean region. The data were grouped in terms of altitude, dominant exposure, vegetation height, and mean age factors, and it is tried to reveal the change of maquis biomass depending on these factors. The data obtained shown significant variation and, for this reason, the mass values are expressed as mean values. The potential relationship between the mentioned factors and the amounts of stored biomass was examined by using t-test and variation analysis. The mean aboveground biomass amount was found to be 24,183 ton/ha, while mean belowground biomass that doesn't contain fine root was found to be 41,062 ton/ha. According to these results obtained from mean values, the root/shoot ratio was calculated to be 1.7.
Keywords: Biomass; Maquis; Root/Shoot Ratio; Altitude; Exposure